Analyzing Supporting and Inhibiting Factors in the Implementation of Stunting Reduction Acceleration Policy in Depok City - Suri, Supian; Hamdi, Muchlis; Nurdin, Ismail; Lukman, Sampara; Sidiq, Fathir Fajar (International Journal of Science and Society, 2024)
This research raises the issue of stunting, which is not only a serious public health challenge in Depok City but also worldwide. The main focus of the research is to identify and analyze the factors that support and hinder the implementation of policies to accelerate stunting reduction in Depok City and formulate an optimal implementation model. Using a descriptive qualitative approach, this study collected data through in-depth interviews, Focus Group Discussions (FGDs), and observations. The analysis was conducted using NVivo 14 software by applying Knill and Tosun's determinants of policy implementation approach. Results show that factors such as political will, program innovation, human resource quality, and social acceptance are key enablers, while budget inefficiency and sectoral ego were found to be the main inhibitors. The proposed implementation model integrates policy instruments, policy design, control structure, institutional design, administrative capacity, and social acceptance with a focus on sustainability. This research makes an important contribution to the development of knowledge in the fields of government science and public administration and the practice of public policy, particularly in efforts to accelerate stunting reduction in Depok City and other regions in Indonesia.